2019
DOI: 10.1139/cjpp-2018-0528
|View full text |Cite
|
Sign up to set email alerts
|

Ambroxol attenuates cisplatin-induced hepatotoxicity and nephrotoxicity via inhibition of p-JNK/p-ERK

Abstract: Hepatotoxicity and nephrotoxicity are important drawbacks of cisplatin. The objective of this study is to evaluate the ability of ambroxol in 2 different doses (35 and 70 mg/kg, i.p.) to protect liver and kidney from damage induced by a single dose of cisplatin (10 mg/kg, i.p.) in comparison with N-acetylcysteine (250 mg/kg, i.p.). Inflammatory, oxidative stress, and apoptotic biomarkers were investigated to show the influence of ambroxol on hepatotoxicity and nephrotoxicity. Ambroxol decreased the elevated ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 35 publications
2
12
0
Order By: Relevance
“…Increased level of MDA and reduction in antioxidant status (GSH, GPx, SOD, and catalase) were observed in the cisplatin treated rats and this is in agreement with previous studies, i.e. Bishr and colleagues (2018[ 13 ]) as well as Ahmadipour and colleagues (2015[ 3 ]). GSH plays an important role in the detoxification of cisplatin and cell death occurs when GSH is markedly exhausted (Ince et al, 2014[ 41 ]).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Increased level of MDA and reduction in antioxidant status (GSH, GPx, SOD, and catalase) were observed in the cisplatin treated rats and this is in agreement with previous studies, i.e. Bishr and colleagues (2018[ 13 ]) as well as Ahmadipour and colleagues (2015[ 3 ]). GSH plays an important role in the detoxification of cisplatin and cell death occurs when GSH is markedly exhausted (Ince et al, 2014[ 41 ]).…”
Section: Discussionsupporting
confidence: 92%
“…β-Caryophyllene served as positive control. All animals except for those in the control group and PmEO400 group were administered with a single dose of cisplatin (10 mg/kg) intraperitoneally (Bishr et al, 2018[ 13 ]) on day 15, left untreated for three days and were sacrificed humanely on day 18 (Palipoch and Punsawad 2013[ 63 ]). Blood samples were collected via cardiac puncture, whereas liver was excised for further analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Here, the present study showed for the first time that MOR/CP combination enhanced of hepatic inflammation by inducing TNF-α/IL-6 pathway. The present study also showed that CP induced apoptosis by up-regulating caspase 3, which was expected from previous studies [3,6,23]. MOR alone also up-regulated caspase 3 in the liver.…”
Section: Discussionsupporting
confidence: 91%
“…7 Cisplatin is an effective treatment but causes nephrotoxicity. [8][9][10] Carboplatin, by contrast, exhibits cytotoxicity against ovarian cancer cells without obvious nephrotoxicity. 11,12 However, resistance to carboplatin is a major obstacle to achieving satisfactory effects in ovarian cancer treatment.…”
Section: Introductionmentioning
confidence: 99%